Position Replacement By Inheritee Who Refuses A Heritage According To Heir Civil Law Dan Islamic Heir Law - Gibtha Wilda Permatasari; Yuliati Yuliati; Herman Suryokumoro (Unram Law Review, 2018)
This research journal discusses legal issues relating to the substitution of places made by the heirs who previously rejected the inheritance which falls to him by comparison of the perspectives of civil inheritance law and Islamic inheritance law. Pursuant to Article 848 and Article 1060 of the Civil Code on the replacement of the place by the heirs who reject the inheritance and the notary's role as a general official in providing legal certainty to prevent the issue of inheritance according to the law of civil inheritance and the Islamic inheritance law. The purpose of this research is to know and to analyze whether or not the heirs who have rejected inheritance replace other heirs as well as to know the role of notary in giving legal certainty to prevent problems in the civil inheritance law and Islamic inheritance law. The research method used by the writer is the statue approach and comparative approach. Heirs who reject inheritance under civil law of inheritance cannot change place (plaatsvervulling) because the requirement of replacement of place according to the law of civil inheritance is derived from families of blood in the same degree and not reject the inheritance. The replacement of places in Islamic inheritance law is known as mawali however, Islamic law does not recognize the denial of inheritance only known in the law of civil inheritance.